2018
DOI: 10.1177/0198742917746633
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Functional (Behavioral) Assessment

Abstract: In the early 1990s, our group at the University of South Florida initiated a series of studies designed to develop, evaluate, and demonstrate a function-based approach to school-based interventions for the problem behaviors of elementary students with severe emotional and behavioral disorders. Our first step into this research topic was an intensive case study with a 12-year-old girl, "Jill," who had multiple disability labels, including severe emotional disturbance, and whose behavioral challenges had proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…ADHD = attention-deficit/hyperactivity disorder; CEQ = Credibility/Expectancy Questionnaire; IRS = Impairment Rating Scale; ODD = oppositional defiant disorder; RSES = Rosenberg Self-Esteem Scale; STRS = Student-Teacher Relationship Scale; TSES = Teachers' Sense of Efficacy Scale; TTI = Teacher Telephone Interview. (Chronis et al, 2004;Dunlap & Kern, 2018;Ervin et al, 2000;Harrison et al, 2019;Miller & Lee, 2013;Pfiffner et al, 2006). Further, the short and focused nature of our intervention may have added to large effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD = attention-deficit/hyperactivity disorder; CEQ = Credibility/Expectancy Questionnaire; IRS = Impairment Rating Scale; ODD = oppositional defiant disorder; RSES = Rosenberg Self-Esteem Scale; STRS = Student-Teacher Relationship Scale; TSES = Teachers' Sense of Efficacy Scale; TTI = Teacher Telephone Interview. (Chronis et al, 2004;Dunlap & Kern, 2018;Ervin et al, 2000;Harrison et al, 2019;Miller & Lee, 2013;Pfiffner et al, 2006). Further, the short and focused nature of our intervention may have added to large effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…FBA is the process of collecting data to evaluate the relations between events in the environment and specific behaviors (Dunlap & Kern, 2018) and is conducted as a first step to developing behavior intervention plans based on the function of the targeted behavior (Drasgow, Yell, Bradley, & Shriner, 1999). For more than two decades, SCD studies with researchers conducting the FBA have found strong effects when interventions were selected based on the identified function (Crone, Hawken, & Bergstrom, 2007;Dunlap, Kern-Dunlap, Clarke, & Robbins, 1991).…”
Section: Functional Behavioral Assessmentmentioning
confidence: 99%
“…Given the variability of behavioral interventions with this population, more research is needed to determine if these results are replicable and generalizable. Furthermore, as recommended by Dunlap and Kern (2018), experts need to evaluate methods for making the FBA process more efficient, feasible, and acceptable for educator implementation.…”
Section: Moderatorsmentioning
confidence: 99%
“…There is emerging evidence demonstrating that teachers can improve their classroom management practices through structured consultative approaches and applied practices embedded into more traditional in-service PD (Codding, Livanis, Pace, & Vaca, 2008). Yet, few studies have examined methods to systematically train educators how to implement functional approaches to assessment and intervention (Conroy, Alter, & Scott, 2009; Dunlap & Kern, 2018; Umbreit, Ferro, Liaupsin, & Lane, 2007).…”
Section: Fabismentioning
confidence: 99%